2020
DOI: 10.1177/0032321720936049
|View full text |Cite
|
Sign up to set email alerts
|

The Right Men: How Masculinity Explains the Radical Right Gender Gap

Abstract: The radical right is disproportionately supported by men, yet there is little research on masculinity’s role in creating this discrepancy. This article breaks new ground in using masculinity as an analytical construct to explain the gender gap in one of the UK’s most significant radical right organisations: the English Defence League. Drawing on original qualitative data and interviews with past and present English Defence League activists, this article argues that English Defence League beliefs and practices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 72 publications
(81 reference statements)
0
26
0
1
Order By: Relevance
“…If it is not necessarily the ideological positions of radical‐right parties – that is their nativism, anti‐minority and anti‐liberal authoritarianism – that deter women from supporting and voting for them, why is there a RRGG? One hypothesized, yet under‐researched explanation for this gap is that it lies, at least in part, in the gendered image of the radical‐right (Ralph‐Morrow 2020). Research on party stereotypes has shown that right‐wing parties are often portrayed in the media, and are identified by the public, with certain masculine stereotypes (tough, authoritarian, aggressive/assertive, concerned with ‘hard’ issues etc.…”
Section: The Radical‐right Gender Gapmentioning
confidence: 99%
See 1 more Smart Citation
“…If it is not necessarily the ideological positions of radical‐right parties – that is their nativism, anti‐minority and anti‐liberal authoritarianism – that deter women from supporting and voting for them, why is there a RRGG? One hypothesized, yet under‐researched explanation for this gap is that it lies, at least in part, in the gendered image of the radical‐right (Ralph‐Morrow 2020). Research on party stereotypes has shown that right‐wing parties are often portrayed in the media, and are identified by the public, with certain masculine stereotypes (tough, authoritarian, aggressive/assertive, concerned with ‘hard’ issues etc.…”
Section: The Radical‐right Gender Gapmentioning
confidence: 99%
“…Furthermore, we hypothesize that the gender mainstreaming effect should work particularly well among women. We hypothesize that because women may be more cognizant of, and deterred by, the radical‐right's masculinist image (Ralph‐Morrow 2020), the counterstereotypes presented by a woman politician or activist on the radical‐right should have a greater effect on women, compared to men. However, we argue that this is not simply a gender affinity effect (Dolan 2008; Goodyear‐Grant & Croskill 2011) whereby women are simply more likely to support women in politics.…”
Section: The Role Of Gender Stereotypes In Mainstreaming the Radical‐rightmentioning
confidence: 99%
“…Sociodemographic characteristics. Scholarship suggests that older men with low formal education and little personal contact with science are more likely to harbor populist attitudes toward science [6,36,37]. Members of this milieu could be understood as "losers of automation" who fear that scientific and technological innovations threaten their socioeconomic position [38], worry that certain sciences and humanities erode cultural values [39], and avoid personal relationships with scientists as they see them as a distant elite [19].…”
Section: Science-related Populist Attitudes and Explanatory Factorsmentioning
confidence: 99%
“…Подобный антагонизм, думается, в скором времени станет центральным для общественно-политического дискурса современной Европы, поскольку, как подчеркивает ряд исследователей правого радикализма, в частности М. Кайяни и П. Крель [Caiani, Kroll 2017], Й. Ридгрен [Rydgren 2013], К. Мюдде ], неотъемлемой чертой праворадикальной идеологии является социокультурный авторитаризм, который включает в себя декларации о жесткой приверженности закону и порядку, а также уважительное отношение к семейным ценностям. Кроме того, отдельного внимания исследователей в последние годы заслуживает тема взаимосвязи гендерной проблематики и праворадикального дискурса как в целом ], так и в рамках британского случая [Ralph-Morrow 2020].…”
Section: партии в политике…unclassified